Comparative Decellularization and Recellularization of Normal Versus Streptozotocin‐Induced Diabetes Mellitus Rat Pancreas. Issue 4 (28th October 2018) - Huang, Ying‐Bao; Mei, Jin; Yu, Yaling; Ding, Yuqiang; Xia, Weizhi; Yue, Ting; Chen, Weijian; Zhou, Meng‐Tao; Yang, Yun‐Jun
Abstract: Decellularized (DC) organs/tissues offer a promising scaffold for regenerative bioengineering. However, it is not clear whether the diabetic mellitus (DM) pancreas can be used in decellularized and recellularized bioengineering. For assessment of these questions, murine pancreatic scaffolds of normal, type 1DM (T1DM) and type 2 DM (T2DM) pancreas were generated using a perfusion decellularization technique and assessed by histology, scanning electron microscopy, immunohistochemistry, and enzyme‐linked immunosorbent assay (ELISA). The capacity of DC pancreatic scaffolds to support attachment and proliferation of human umbilical vein endothelial cells (HUVECs) and MIN‐6 β cells was also assessed. Our results showed that DC pancreatic scaffolds were successfully produced from T1DM and T2DM pancreas and maintained their extracellular matrix (ECM) composition, 3D ultrastructure, and various cytokines. All of the pancreatic scaffolds were sufficiently cytocompatible and were able to support proliferation and adhesion of HUVECs and MIN‐6 β cells. The preliminary results support the biological utility of diabetes mellitus pancreatic scaffolds and pave the way for further investigations to assess the potential ability of using diabetes mellitus pancreas as scaffolds for recellularization and eventual medical applications.